PENGARUH INEFFECTIVE MONITORING, FINANCIAL STABILITY, DAN CORPORATE GOVERNANCE, TERHADAP FINANCIAL STATEMENT FRAUD - Sherly Advent Obidience Ndruru; Joan Yuliana Hutapea (Fakultas Ekonomi Universitas Advent Indonesia, 2022)
This study has an aim in finding out whether Financial Statement Fraud can be influenced by Ineffective Monitoring (X1), Financial Stability (X2), and Corporate Governance (X3), in Consumer Goods Industry Sector that listed on the Indonesia Stock Exchange in 2018-2021. In measuring the financial statement fraud, this study research use Beneish M-Score Model. Collecting the data used secondary method from the audited annual report based on IDX through www.idx.co.id. In this study, the sampling method used purposive sampling with a total sample of 132 companies and using logistic regression analysis model. Based on analysis that made, resulted Financial Statement Fraud is not significantly affected by Ineffective Monitoring, Financial Statement Fraud is significantly affected by Financial Stability, Financial Statement Fraud is significantly affected by Corporate Governance. In simultaneous, the variables are significantly affecting the Financial Statement Fraud.